Adaptive nodes algorithm to solve the orphan nodes problem in a ZigBee Tree WSN (2021)
We have developed an algorithm based on hybrid nodes composed of an XBee S2C module configured in API mode with escape and connected to a microcontroller ATMEGA 328P to solve the orphan node problem of a ZigBee tree topology. The sensor nodes have both features End Device and Router that may alternate depending on the situation, and the node can adapt itself to keep the network integrality as much as possible. On the other hand, the coordinator node comprises an XBee S2C module and the embedded system Raspberry Pi 3, which hosts the algorithm and is set up as an access point, a database server, and a web server. Using the proposed algorithm, we were able to recover up to 42.8% of the network coverage, but it comes with an energy cost due to the switch from End Device to Router. Additionally, a mobile application integrated with notification service and Google Maps was developed to monitor every node’s behavior in the Wireless Sensor Network.